KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KEPULAUAN TANIMBAR (Studi Kasus: Dinas Pendapatan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Kepulauan Tanimbar) - Albertus Lalaun; Victor Cornelis, Theofilus Josias F. K. Matrutty (Jurnal Ekonomi dan Bisnis, 2025)
Regional taxes in Tanimbar Islands Regency consist of hotel taxes, restaurant taxes, entertainment taxes, billboard taxes, street lighting taxes, parking taxes, non-metallic minerals and rocks, rural and urban land and building taxes, and land and building rights acquisition duties. This study aims to find out the amount of regional tax contribution to the original regional income of Tanimbar Islands Regency. This research is located in Tanimbar Islands Regency as a place or research object is a report on the realization of original income in the Tanimbar Islands Regency. Secondary data obtained is in the form of original revenue data for the Tanimbar Islands Regency in 2018-2022. The data was then analyzed using contribution analysis. . The results of the study show that the Regional Taxes that provide the highest average contribution during 2018 to 2022 are: Street Lighting Tax of 13.92%, Non-Metallic Mineral and Rock Tax of 12.53%, Restaurant Tax of 2.99%, Rural and Urban Land and Building Tax of 2.37%, Billboard Tax of 1.42%, Hotel Tax of 0.93%, Land and Building Rights Acquisition Duty of 0.62%, Entertainment Tax of 0.05%, Parking Tax of 0.001%.